a,(3x - 2)3 = 64
b,18 ⋮ x; 24 ⋮ x và x là số tự nhiên lớn nhất
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. ( 3x - 4 ) . 23 = 64
( 3x - 4 ) . 2 = 4
3x - 4 = 2
3x = 6
x= 2
b. 2x = 32
2x = 25
x = 5
a) \(\Leftrightarrow x^2-36=64\)
\(\Leftrightarrow x^2=100\)
\(\Leftrightarrow x=\pm10\)
Vậy \(x=\pm10\)
b) \(\Leftrightarrow x^2-x-3x+3=0\)
\(\Leftrightarrow x\left(x-1\right)-3\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x-3=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=3\end{matrix}\right.\)
Vậy \(x\in\left\{1;3\right\}\)
`a)(x+5)^3=-64`
`(x+5)^3=(-4)^3`
`x+5=-4`
`x=-4-5=-9`
Vậy `x=-9`
`2)(2x-3)^3=8`(9 không được)
`(2x-3)^3=2^3`
`2x-3=2`
`2x=5`
`x=5/2`
Vậy `x=5/2`
a,(x + 3)2 - (x - 3)2 = 6x + 18
=> x^2 + 6x + 9 - x^2 + 6x - 9 = 6x + 19
=> 12x - 6x = 19
=> 6x = 19
=> x = 19/6
a: =>9x^2+12x+4-9x^2+12x-4=5x+38
=>24x=5x+38
=>19x=38
=>x=2
e: =>x^3+1-2x=x^3-x
=>-2x+1=-x
=>-x=-1
=>x=1
f: =>x^3-6x^2+12x-8+9x^2-1=x^3+3x^2+3x+1
=>12x-9=3x+1
=>9x=10
=>x=10/9
b: \(\Leftrightarrow3x^2-12x+12+9x-9=3x^2+3x-9\)
=>-3x+3=3x-9
=>-6x=-12
=>x=2